Rheological, Sensory And Shelf Life Study Of Texture-Modified Chicken Rendang For The Elderly With Dysphagia - Abu Zarim, Nuraihan (2020)
This study involves rheological, sensory, and shelf life analysis of texture-modified chicken rendang (TMCR) as part of the development process to introduce a ready-to-eat food for the elderly with dysphagia in Malaysia